SUSTAINABILITY, GREEN BONDS DAN DAMPAKNYA PADA NILAI PERUSAHAAN - Dharmastuti, Christiana Fara; sumani, sumani; Zefanya, Okaria Nathalie (Universitas Katolik Indonesia Atma Jaya, 2024)
Sustainability issues and practices have now become an important part and an interesting trend around the world. Companies in running their business are required not only to take into account economic factors, but also to pay attention to sustainability practices. In the financial sector, one of the sustainability supports through funding through green bonds, namely green bonds. This study aims to analyze the effect of corporate sustainability practices in terms of the 3 P's (Profit, Planet, People) on the decision to issue green bonds and their impact on company performance. The study was conducted on companies in ASIA with the subject of 78 companies from 10 countries. Data was obtained from the Climate Bonds Initiative, International Capital Market Association, IDX and Yahoo Finance and from the company's website. Hypothesis testing using the Smart PLS application. The test results show that people affect the decision of green bonds and company performance, while profit and planet have no significant effect on green bonds or company performance.